Difficulties in Writing News Item Experienced by Students of A Vocational High School in Cirebon - Syahfitri Anugerah Dewi; Misdi Misdi (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
This study was qualitative research that used descriptive analysis.The present study aimed at investigating out the students’ difficulties in writing news item and find out the most dominant difficulty in writing news item made by the eleventh graders of SMK Muhammadiyah Kedawung.in academic year of 2017/2018. The first research question was answered by taking 5 students at random to be analyzed to investigate students’ ability in writing news item text. Students faced four types of difficulty such as agreement, preposition, and article. In agreement, it was found that all the difficulties are omitting and misusing the verbs and helping verbs of the sentence. Furthermore, to find the main difficulty in writing news item was to analyze 22 result of test. Based on the data analysis, punctuation was the most difficult aspects in writing proved by having 222 cases or 61% of cases. Spelling had 77 cases or 21% of cases. Proposition had 27 or 8% of cases on omitting prepositions. Agreement had 23 or 6% of cases on ignoring and misusing verbs of the sentences in their writings. Article had 15 or 4% of cases on ignoring the definite and indefinite article. In conclusion, it is suggested for English teachers to increase students’ motivation in learning English, especially in writing news item text, and to make the students easier to understand and comprehend the material so the difficulties in grammar and mechanic can be decreased.